Membrane-Delimited Phosphorylation Enables the Activation of the Outward-Rectifying K Channels in Motor Cell Protoplasts of Samanea saman. - Moran, N. (1996)
Outward-rectifying K channels activated by membrane depolarization (Kout or KD channels) control K+ efflux from plant cells. To find out to what extent phosphorylation is required for the activity of these channels, the patch-clamp method was applied to protoplasts from the legume Samanea saman in both whole-cell and isolated-patch configurations. In the absence of either Mg2+ or ATP in the "cytosolic" solution, the KD channel activity declined completely within 15 min. This decline could be reversed in excised, inside-out patches by restoring MgATP (1 mM) to the cytoplasmic side of the membrane. Mg2+ (1 mM) plus 5[prime]-adenylylimidodiphosphate (1 mM), a nonhydrolyzable ATP analog, did not substitute for ATP. Mg2+ (1 mM) plus adenosine 5[prime]-O-(3-thiotriphosphate) (25 to <100 [mu]M), an irreversibly thiophosphorylating ATP analog, sustained channel activity irreversibly. 1-(5-IsoquinolinesulphonyI)-2- methylpiperazine (100 [mu]M), a broad-range kinase inhibitor, blocked the activity of KD channels in the presence of MgATP. These results strongly suggest that the activation of the outward-rectifying K channels by depolarization depends critically on phosphorylation by a kinase tightly associated with the KD channel.